1, 25-Dihydroxyvitamin D3 modulates calcium transport in goat mammary epithelial cells in a dose- and energy-dependent manner. Issue 1 (December 2016) - Sun, Feifei; Cao, Yangchun; Yu, Chao; Wei, Xiaoshi; Yao, Junhu
Abstract Background Calcium is a vital mineral and an indispensable component of milk for ruminants. The regulation of transcellular calcium transport by 1, 25-dihydroxyvitamin D3 (1, 25-(OH)2 D3, the active form of vitamin D) has been confirmed in humans and rodents, and regulators, including vitamin D receptor (VDR), calcium binding protein D9k (calbindin-D9k ), plasma membrane Ca2+ -ATPase 1b (PMCA1b), PMAC2b and Orai1, are involved in this process. However, it is still unclear whether 1, 25-(OH)2 D3 could stimulate calcium transport in the ruminant mammary gland. The present trials were conducted to study the effect of 1, 25-(OH)2 D3 supplementation and energy availability on the expression of genes and proteins related to calcium secretion in goat mammary epithelial cells. Methods An in vitro culture method for goat secreting mammary epithelial cells was successfully established. The cells were treated with different doses of 1, 25-(OH)2 D3 (0, 0.1, 1.0, 10.0 and 100.0 nmol/L) for calcium transport research, followed by a 3-bromopyruvate (3-BrPA, an inhibitor of glucose metabolism) treatment to determine its dependence on glucose availability. Cell proliferation ratios, glucose consumption and enzyme activities were measured with commercial kits, and real-time quantitative polymerase chain reaction (RT-qPCR), and western blots were used to determine the expression of genes and proteins associated with mammary calcium transport in dairy goats, respectively. Results 1, 25-(OH)2 D3 promoted cell proliferation and the expression of genes involved in calcium transport in a dose-dependent manner when the concentration did not exceed 10.0 nmol/L. In addition, 100.0 nmol/L 1, 25-(OH)2 D3 inhibited cell proliferation and the expression of associated genes compared with the 10.0 nmol/L treatment. The inhibition of hexokinase 2 (HK2), a rate-limiting enzyme in glucose metabolism, decreased the expression of PMCA1b and PMCA2b at the mRNA and protein levels as well as the transcription of Orai1, indicating that glucose availability was required for goat mammary calcium transport. The optimal concentration of 1, 25-(OH)2 D3 that facilitated calcium transport in this study was 10.0 nmol/L. Conclusions Supplementation with 1, 25-(OH)2 D3 influenced cell proliferation and regulated the expression of calcium transport modulators in a dose- and energy-dependent manner, thereby highlighting the role of 1, 25-(OH)2 D3 as an efficacious regulatory agent that produces calcium-enriched milk in ruminants when a suitable energy status was guaranteed.